PENGARUH MODEL PEMBELAJARAN KOLABORATIF BERBASIS LESSON STUDY LEARNING COMMUNITY (LSLC) - Marhamah Marhamah; Mustafa Mustafa; Melvina Melvina (FKIP Unsyiah, 2017)
This research to determine whether or not the influence of Collaborative Learning model Based on Lesson Study Learning Communiy (LSLC) on the results of students' learning grade VIII MTsN Samalanga. The population of this research is all students of grade VIII MTsN Samalanga. While to determine the sample used purposive sampling technique. So the sample of this research is class VIIIA which amounted to 31 people (experiment class) and class VIIIB which amounted to 31 people (control class). The method used is quasi experimental research method (quasi experimental). Data collection is done through documentation and tests. Based on the results of data analysis obtained t_hitung t_tabel is 5.60 1.67 then Ho is rejected. In the experimental class students do sharing task and jumping task, so that the collaboration and student learning outcomes increase. So it can be concluded that the lesson learning learning commuity (LSLC) collaborative learning model has an effect on the students' achievement of grade VIII MTsN Samalanga.